The Use of Cryopreserved Biological Material for Water Quality Assessment - Paredes, Estefania; Bellas, Juan (Frontiers in Marine Science, 2019)
The stated aim of this perspective article is to present new developments and discuss future directions on the applications of cryopreserved organisms to marine water quality assessment. To facilitate this, the authors provide a background of essential knowledge of cryopreservation when applied to ecotoxicology, as well as, practical examples available in literature. An integrated approach with combined monitoring of chemical status plus measurements of biological effects has been recommended extensively by international institutions for the assessment of marine pollution. Among the available techniques, bioassays have been considered as sufficiently robust to be incorporated in marine pollution monitoring programs. However, the routine application of bioassays has also allowed the identification of one of the factors that limits a more extensive use of such biological methods: the availability of biological material throughout the year, regardless of natural spawning periods. A solution to this limitation is the application of cryopreservation techniques. Cryopreservation may, for instance, provide access to stable quality biological material when test species are out of the reproductive season, without the need for maintaining and conditioning organisms in the laboratory. It also guarantees access to a large variety of species that might not be available at the same time of the year and, on top of that, cryopreservation provides opportunities to laboratories that might not have the facilities to keep all these organisms in culture.